The motivation level of learning chemistry among secondary school students - Zuraimi, Farhanawati (2015)
Students enrolment in chemistry course are decreasing from elementary school towards higher education level. Studies made by some researchers issues several factors that lead to student’s motivation towards the subjects itself. Many researchers found out that, the lack of motivation among students are oriented in cognitive, affective and conative aspect. Students are not cognitively motivated if they’re facing the lack of understanding in the content and purpose of the activity done in the learning process. An affective motivation in learning are referring to the emotional and value of the subject learned whilst conative aspect are more focusing on willingness and effort made by students in achieving their target in their learning process. All of these three aspect of motivation must not been taken for granted in order to enhance students interest in chemistry subject not just in school but also towards higher education level.